High-affinity adsorption leads to molecularly ordered interfaces on TiO2 in air and solution - Balajka, Jan; Hines, Melissa A; DeBenedetti, William J I; Komora, Mojmir; Pavelec, Jiri; Schmid, Michael; Diebold, Ulrike (Science (New York, N.Y.), 2018)
Researchers around the world have observed the formation of molecularly ordered structures of unknown origin on the surface of titanium dioxide (TiO2) photocatalysts exposed to air and solution. Using a combination of atomic-scale microscopy and spectroscopy, we show that TiO2 selectively adsorbs atmospheric carboxylic acids that are typically present in parts-per-billion concentrations while effectively repelling other adsorbates, such as alcohols, that are present in much higher concentrations. The high affinity of the surface for carboxylic acids is attributed to their bidentate binding. These self-assembled monolayers have the unusual property of being both hydrophobic and highly water-soluble, which may contribute to the self-cleaning properties of TiO2 This finding is relevant to TiO2 photocatalysis, because the self-assembled carboxylate monolayers block the undercoordinated surface cation sites typically implicated in photocatalysis.